Governance Capacity dalam Tranfromasi Digital Pemerintah Daerah Kabupaten Banggai - Irwansyah Kamindang (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Digital transformation in government through the Electronic-Based Government System (SPBE) has become an important strategy for improving effectiveness, efficiency, transparency, and service quality. The success of digital transformation is not determined solely by the availability of technology, but also by governance capacity, which includes the government’s ability to manage institutions, human resources, technological infrastructure, information security, and integrated financial support. This study aims to analyze the governance capacity of the Regional Government of Banggai Regency in supporting digital transformation. This study employs a qualitative approach using a literature study method by analyzing various policy documents, government reports, scholarly articles, and other relevant secondary sources. The findings indicate that the governance capacity of the Regional Government of Banggai Regency is relatively strong, as reflected in its 2024 SPBE Index score of 3.58, categorized as Very Good. This achievement is supported by Banggai Regent Regulation Number 65 of 2023, the SPBE Coordination Team, Banggai Smart City, Banggai Command Center, and the Satu Data Banggai program. Nevertheless, several weaknesses remain in the aspects of SPBE governance and management, particularly regarding ICT audits, monitoring and evaluation, information security, the equal distribution of digital competencies among civil servants, system integration, and budget limitations. The findings of this study show that the success of digital transformation is strongly influenced by institutional coordination capacity and organizational learning capability, thereby broadening the perspective of governance capacity in the study of local government digital transformation.